2008
DOI: 10.1107/s1600536808018655
|View full text |Cite
|
Sign up to set email alerts
|

Trimesic acid dimethyl sulfoxide solvate: space group revision

Abstract: The structure of the title solvate, C9H6O6·C2H6OS, was determined 30 years ago [Herbstein, Kapon & Wasserman (1978 ▶). Acta Cryst. B34, 1613–1617], with data collected at room temperature, and refined in the space group P21. The present redetermination, based on high-resolution diffraction data, shows that the actual space group is more likely to be P21/m. The crystal structure contains layers of trimesic acid molecules lying on mirror planes. A mirror plane also passes through the S and O atoms of the solvent… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

0
8
0

Year Published

2010
2010
2020
2020

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 10 publications
(8 citation statements)
references
References 4 publications
0
8
0
Order By: Relevance
“…On the other hand, many ligands used in MOF synthesis can form hydrogen bonds. Indeed, DMSO is known to form a hydrogen bonded solvate structure with the trimesic acid ligand 12. The relative contributions of these solute–solvent interactions to the prevention of nucleation at room temperature are not clear at present.…”
Section: Methodsmentioning
confidence: 99%
“…On the other hand, many ligands used in MOF synthesis can form hydrogen bonds. Indeed, DMSO is known to form a hydrogen bonded solvate structure with the trimesic acid ligand 12. The relative contributions of these solute–solvent interactions to the prevention of nucleation at room temperature are not clear at present.…”
Section: Methodsmentioning
confidence: 99%
“…A monosolvate of TMA and DMSO (refcode TMADMS) was discovered in 1978 by Herbstein et al 8 The crystals were obtained by slow cooling crystallisation of TMA in water-DMSO (8 mol%) solution and belonged to the monoclinic space group P2 1 (Z = 4). In 2008 Bernes et al 9 revised the space group to P2 1 /m (refcode TMADMS01, for unit cell dimensions see Table 1).…”
mentioning
confidence: 99%
“…For the majority of the other solvents, the known α-form of TMA was observed. The solvents in which there were differences were those known solvated forms of TMA, e.g., DMSO [20][21][22] and pentanol [7] (for LAG) and water [18,19], methanol [9], butanol (for the slurry) [7] (Figures S1 and S2). We found that the technique used was a factor in our observation of the phases, for example, the butanol solvate and hydrate were not observed after LAG, but we did begin to observe these phases forming under slurry.…”
Section: Solid Form Screenmentioning
confidence: 99%